Religious Relations on Social Media: Hadith Verification, Hoax News and Forward Quote of Religious Advice - Beni Ahmad Saebani; Adib Gunawan (Asyahid Journal of Islamic and Quranic Studies (AJIQS), 2022)
Nowadays there is a phenomenon, where there is news or chain reports circulating in the media whose truth is invalid. This invalidity can be in the form of content that is not in accordance with the original, whether in the form of what, where, when, and who was involved in the reporting. Not only that, sometimes the title seems to have bias in it. This is from the side of the news source. It doesn't stop there, in terms of people's behavior it also shows its own uniqueness, namely that they easily pass on the news without first checking and checking the truth of the news. Finally, the invalid news, which we call a hoax, spread very quickly via FB, Twitter, IG, WAG, etc. How Islamic caution first used to verify and convey news. Apart from that, we will also invite readers to see the method of practicing good and evil, preaching in accordance with the recommendations of religious scholars based on the Koran and Alhadist. The results obtained are that passing on religious content advice on social media is not as easy and simple as the intention to preach and preach good and evil, because in it there are religious boundaries that must be taken into account, including whether the religious content is valid or not, and the party giving advice has done so or not. Keywords: Hoax, Islam, social media Abstrak Dewasa ini ada fenomena, di mana ada berita atau kabar berantai yang beredar di media yang kebenarannya tidak sahih. Tidak sahih tersebut bisa dalam bentuk isi yang tidak sesuai dengan aslinya, baik berupa apa, di mana, kapan, dan siapa yang terlibat dalam pemberitaan tersebut. Tidak hanya itu, terkadang judul yang dibuat terkesan ada bias di dalamnya. Ini dari sisi sumber berita. Tidak berhenti di situ, dari sisi perilaku masyarakat juga memperlihatkan keunikan tersendiri, yaitu dengan mudahnya meneruskan berita tersebut tanpa terlebih dahulu memberikan cek dan ricek akan kebenaran berita tersebut. Akhirnya, berita yang tidak sahih tersebut yang kita sebut sebagai hoax tersebar begitu cepatnya menyebar via FB, twitter, IG, WAG, dan lain-lain. Bagaimana kehati-hatian Islam pertama dulu memverifikasi dan menyampaikan berita. Selain itu kami juga akan mengajak pembaca untuk melihat bagaimana metode dalam beramar ma’ruf nahi munkar, berdakwah yang sesuai dengan anjuran dari para alim ulama berdasarkan Alquran dan Alhadist. Diperoleh hasil bahwa meneruskan nasihat-nasihat konten agama dalam media sosial tidak semudah dan sesederhana dengan alasan niat untuk berdakwah dan beramar ma’ruf nahi munkar, karena di dalamnya ada batas-batas agama yang harus diperhatikan, diantaranya adalah konten agama tersebut sahih atau tidak, dan pihak yang memberi nasihat sudah melakukan atau belum. Kata kunci: Hoaks, Islam, media sosial